(untitled) (Proceedings of the International Conference on Education, 2025)
Former women migrant workers have great potential from their work experience abroad, but it is often not utilized optimally. The existing empowerment tends to focus on technical training without considering their unique needs and experiences. As adult individuals with diverse experiences and knowledge, former migrant workers have the capacity to empower themselves if supported by an experiential learning approach. This research analyze the application of Experiential Learning (EL) in empowering former women migrant workers in the Desa Peduli Buruh Migran (DESBUMI) community. With a case study design, data were collected through observation, interviews, and documentation. The results show that experiential learning helps participants integrate personal experiences into a relevant and contextual learning process. This approach effectively enhances entrepreneurial skills, business management, financial decision-making, and strengthens community economic networks and social solidarity. Reflection and direct application are key in contextualizing knowledge. These findings offer a replicable experiential learning model and recommend the integration of the EL approach into empowerment programs to drive sustainable social transformation.